A Thermophilic Tetramolecular G‐Quadruplex/Hemin DNAzyme. Issue 52 (30th November 2017) - Guo, Yuehua; Chen, Jielin; Cheng, Mingpan; Monchaud, David; Zhou, Jun; Ju, Huangxian
Abstract: The quadruplex‐based DNAzyme system is one of the most useful artificial enzymes or catalysts; their unique properties make them reliable alternatives to proteins for performing catalytic transformation. The first prototype of a thermally stable DNAzyme system is presented. This thermophilic DNAzyme is capable of oxidizing substrates at high temperatures (up to 95 °C) and long reaction times (up to 18 h at 75 °C). The catalytic activity of the DNAzymes were investigated with the standard peroxidase‐mimicking oxidation of 2, 2′‐azino‐bis(3‐ethylbenzothiozoline‐6‐sulfonic acid) (ABTS) by H2 O2 . The step‐by‐step design of this unique heat‐activated G‐quadruplex/hemin catalyst, including the modification of adenines at both ends of G‐tracts, the choice of cation, and its concentration for DNAzyme stabilization, is described. This work investigates thoroughly the molecular basis of these catalytic properties and provides an example of an industrially relevant application. Abstract : G, that's hot : The activity and heat‐resistant properties of tetramolecular G‐quadruplex/hemin DNAzymes can be improved by adenines for application as a catalyst at high temperature. The catalytic activities of the DNAzymes were investigated (up to 95 °C; up to 18 h at 75 °C) with the standard peroxidase‐mimicking oxidation of 2, 2′‐azino‐bis(3‐ethylbenzothiozoline‐6‐sulfonic acid) (ABTS) by H2 O2 .